Phytochemical and Antioxidant Dynamics of the Soursop Fruit (Annona muricata L.) in response to Colletotrichum spp. - Alejandro Rubio-Melgarejo; Rosendo Balois-Morales; Yolotzin Apatzingan Palomino-Hermosillo; Graciela Guadalupe López-Guzmán; José Carmen Ramírez-Ramírez; Edwin Cervantes-García; Brandon Javier Villalobos-Rosario; Pedro Ulises Bautista-Rosales (Journal of Food Quality)
This work evaluates the effect of the pathogens Colletotrichum siamense and C. gloeosporioides on the response of soursop fruits. The bioactive compounds (total phenols, flavonoids, anthraquinones, coumarins, steroids, terpenoids, alkaloids, and saponins) were evaluated qualitatively in soursop pulp. Positive phytochemicals and antioxidant activity (DPPH•, ABTS•+, and FRAP) were quantified at day zero, one, three, and five. Fruits treated with C. gloeosporioides showed higher disease severity (P<0.05). Early fruit response (day one) was observed with both pathogens, increased the concentration of saponins and repressed the production of quercetin 3-O-glucoside (P<0.05). Likewise, C. siamense decreased total soluble phenols and flavonoids and increased antiradical activity DPPH•. Besides, C. gloeosporioides decreased the levels of kaempferol 3-O-rutinoside and ferulic acid (P<0.05). Regarding the late response (day three), both pathogens decreased the concentration of saponins and increased flavonoids and phytosterols (P<0.05). Nevertheless, C. siamense increased the levels of total soluble phenols, p-coumaric acid, kaempferol, and antiradical activity FRAP (P<0.05). Also, C. gloeosporioides repressed the production of quercetin 3-O-glucoside at day five (P<0.05). Soursop fruits had a response to the attack of Colletotrichum during ripening at physicochemical and oxidative levels, which is associated with the production of compounds related to the development inhibition of pathogens. Even so, soursop fruits showed higher susceptibility to C. gloeosporioides and higher sensitivity to the attack of C. siamense.